Faktor Penyebab Perilaku Menyimpang Anak Usia Dini : Studi Kasus pada Beberapa Anak di TK Unggulan An Nur Surabaya - Fitria Dwi Yanti; Ilun Muallifah (Inovasi Pendidikan dan Anak Usia Dini, 2025)
Deviant behavior in early childhood is an issue that needs serious attention, especially when children start to show the habit of using harsh language while interacting with peers. This phenomenon was found at TK Unggulan An Nur Surabaya, where some children tend to use impolite words during play and communication. The aim of this study is to identify the causal factors behind deviant behavior in early childhood, specifically rude speech, and to analyze the influence of family environment, school, peers, and media on such behavior. This research employed a qualitative approach with a case study design. Data were collected through direct observation, interviews with teachers and parents, and documentation from classroom activities. The findings revealed that rude speaking behavior is influenced by permissive parenting, peer group influence, exposure to inappropriate media, and immature emotional regulation. The conclusion is that deviant behavior such as harsh speaking does not arise in isolation but is the result of complex interactions between internal and external factors. Therefore, collaboration between teachers and parents in character education and monitoring of media exposure and peer environment is essential.